Climate change and decadal to centennial-scale periodicities recorded in a late Holocene NE Pacific marine record: Examining the role of solar forcing. - Galloway, J.M.; Wigston, A.; Patterson, R.T.; Swindles, G.T.; Reinhardt, E.; Roe, H.M. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2013)
We present a decadal-scale late Holocene climate record based on diatoms, biogenic silica, and grain size from a 12-m sediment core (VEC02A04) obtained from Frederick Sound in the Seymour-Belize Inlet Complex of British Columbia, Canada. Sediments are characterized by graded, massive, and laminated intervals. Laminated intervals are most common between c. 2948–2708 cal. yr BP and c. 1992–1727 cal. yr BP. Increased preservation of laminated sediments and diatom assemblage changes at this time suggest that cli- mate became moderately drier and cooler relative to the preceding and succeeding intervals. Spectral and wavelet analyses are used to test for statistically significant periodicities in time series of proxies of primary production (total diatom abundance, biogenic silica) and hydrology (grain size) preserved in the Frederick Sound record. Periodicities of c. 42–53, 60–70, 82–89, 241–243, and 380 yrs are present. Results are com- pared to reconstructed sunspot number data of Solanki et al. (2004) using cross wavelet transform to evalu- ate the role of solar forcing on NE Pacific climate. Significant common power of periodicities between c. 42– 60, 70–89, 241–243, and of 380 yrs occur, suggesting that celestial forcing impacted late Holocene climate at Frederick Sound. Replication of the c. 241–243 yr periodicity in sunspot time series is most pronounced be- tween c. 2900 cal. yr BP and c. 2000 cal. yr BP, broadly correlative to the timing of maximum preservation of laminated sedimentary successions and diatom assemblage changes. High solar activity at the Suess/de Vries band may have been manifested as a prolonged westward shift and/or weakening of the Aleutian Low in the mid-late Holocene, which would have diverted fewer North Pacific storms and resulted in the relatively dry conditions reconstructed for the Seymour-Belize Inlet Complex.